The Influence of Resilience and Self Control on Elementary Students’ Social Skills - Siti Fatimah; Yuli Yanti (JEES: Journal of Education and Educational Sciences, 2025)
Despite the central role of social skills in students’ academic and interpersonal success, few studies have examined how internal psychological traits such as resilience and self-control jointly influence these skills in primary education. This study addresses that gap by investigating the influence of resilience and self-control on elementary students’ social skills. Employing a quantitative correlational design, the research involved 240 students from grades IV to VI selected through total sampling. Data were collected through closed questionnaires and analyzed using multiple linear regression. Instrument validity and reliability were tested using SmartPLS version 4.0.9.9, and analysis was conducted with IBM SPSS version 29.0.0.0. Classical assumption tests confirmed the data met normality, multicollinearity, and homoscedasticity criteria. Results indicated that both resilience and self-control had significant and positive effects on social skills, with self-control being the stronger predictor. The model explained 22.5% of the variance in social skills. These findings underscore the need to cultivate students’ internal strengths as part of socio-emotional learning and contribute to the refinement of character education in primary education settings.